2020
DOI: 10.3390/nu12030640
|View full text |Cite
|
Sign up to set email alerts
|

Association between Food Preferences, Eating Behaviors and Socio-Demographic Factors, Physical Activity among Children and Adolescents: A Cross-Sectional Study

Abstract: The prevalence of overweight and obesity is a serious health issue among children and adolescents worldwide. This study aimed to investigate factors influencing weight status-associated food preferences and eating behaviors. A cross-sectional study was conducted to collect data from 2578 pairs of Chinese children and parents in five cities from December 2018 to March 2019. There was an increase in consumptions of processed seafood, nuts and dried fruit/vegetables, and fruit/vegetable juice, but a reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 58 publications
3
18
2
1
Order By: Relevance
“…Our study identified some factors to be the determinants of healthy food preference for Chinese adults. Most determinants were similarly reported in previous studies [7,[23][24][25]. Firstly, our study found that food preferences were strongly influenced by their sociodemographic characteristics.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study identified some factors to be the determinants of healthy food preference for Chinese adults. Most determinants were similarly reported in previous studies [7,[23][24][25]. Firstly, our study found that food preferences were strongly influenced by their sociodemographic characteristics.…”
Section: Discussionsupporting
confidence: 83%
“…Although several studies have published using one-wave cross-sectional survey with focusing on food preference in children or adolescents, studies on food preference of adults are less reported [5][6][7][8]. As children are usually taken care of by their parents, their dietary intake often depends on the family context and their food knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Li Miao found that children from high income family with more pocket money were more likely to be overweight and obesity [41]. however, opposite to previous research [32] lower rate of frequency of eating out was found among children from high-income family, which may be related to the fact that the rate of overweight and obesity was higher among children from high-income family, then they were less likely to eat out . Furthermore, The study showed that in comparison with children in rural regions, children from urban regions tended to be overweight and obesity, and this difference was also found in other domestic studies [ 42,43], which was likely due to the convenience of eating out in the urban regions [44].…”
Section: Discussioncontrasting
confidence: 57%
“…The current study clearly demonstrated the signi cant association between overweight and obesity with higher frequency of eating outside among boys, similar results were observed in previous researches: as in Brazilian children [28], and had been found among children from Etiology of Childhood Obesity (ECHO) study [29], in children and adolescents aged 11-14 years in London Borough [30],in Portugal children [21] and in US elementary schools students [31]. However, we did not observe a signi cant association between obesity and eating out in group of girls, which may due to boys' greater preference for fatty food and girls pay more attention to their weight [32][33][34]. whereas, the result of the UK National Diet and Nutrition Survey (NDNS) indicated that no association between energy intake and frequency of consumption of meals out in children [35].The differences in research result may be partly due to the fact that lacking of uniform standard for the de nition of eating out.…”
Section: Discussioncontrasting
confidence: 45%